Isolation, Partial Purification, and Characterization of Lectins from the Roots of Vigna unguiculata (L.) Walp. - Rivero, Gilda; Camillo, Reginald; Cao, Ernelea; Roderos, Remedios; Matias, Ronald (Science Diliman: A Journal of Pure and Applied Sciences; Vol 7 & 8 (1995-1996), 2007)
A lectin was isolated from the roots of 7-day old Vigna unguiculata (L.) Walp. seedlings using size-exclusion chromatography. The root lectin revealed two subunits in SDS-PAGE and migrated as a single protein in a pH gradient isoelectrofocusing gel electrophoresis as well as in native gel electrophoresis. The root lectin exhibited no specificity to any of the erythrocytes tested. In addition, the agglutinating activity of the root lectin was markedly increased by enzymes. The hemeagglutinating activity of the root lectin was inhibited by the sugars N-acetyl-galactosamine and methyl-a-D-glucopyranoside.